Insulin and Insulin-like Growth Factor signalling (IGF) pathways and cancer / Wan Iryani Wan Ismail, Mohd Nazri Abu, Muhammad Ashraf Mohd Salleh, Izmil Haikal Zainol and Rosmadi Mohd Yusoff - Abu, Mohd Nazri; Mohd Salleh, Muhammad Ashraf; Zainol, Izmil Haikal; Mohd Yusoff, Rosmadi (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2013)
Cell signalling is part of a strategy in drug discovery. Among the focus is by studying the insulin and insulin-like growth factor (IGF1R) signalling pathways. The molecular mechanism of insulin and IGF1R signalling pathways have been studied extensively. Both pathways are vital in many of the mechanisms in human body particularly in regulating the metabolism and cell growth. Besides, both pathways have been found to be involved in numerous diseases such as in various types of cancer. This review briefly revealed the information on the pathways, their correlations and current findings in cancer study.